2010
DOI: 10.1158/1055-9965.epi-10-0027
|View full text |Cite
|
Sign up to set email alerts
|

Fecal MicroRNAs as Novel Biomarkers for Colon Cancer Screening

Abstract: Introduction: Colorectal cancer (CRC) is the second leading cause of cancer-related deaths, but currently available noninvasive screening programs have achieved only a modest decrease in mortality. MicroRNAs (miRNA) play an important role in a wide array of biological processes and are commonly dysregulated in neoplasia. We aimed to evaluate the feasibility of fecal miRNAs as biomarkers for colorectal neoplasia screening.Materials and Methods: Total RNA was extracted from freshly collected stool samples from 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
264
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(284 citation statements)
references
References 27 publications
15
264
1
4
Order By: Relevance
“…In addition, miR-144* and miR-106a were found to be significantly overexpressed in adenomas and in the stool of CRC patients compared with healthy individuals [86,89] . These studies have confirmed that miRNAs from stool samples require validation as diagnostic biomarkers for CRC.…”
Section: Markersmentioning
confidence: 98%
“…In addition, miR-144* and miR-106a were found to be significantly overexpressed in adenomas and in the stool of CRC patients compared with healthy individuals [86,89] . These studies have confirmed that miRNAs from stool samples require validation as diagnostic biomarkers for CRC.…”
Section: Markersmentioning
confidence: 98%
“…Nevertheless, each of the approaches has its own specific advantages and disadvantages. Recently, the findings of miRNAs in body fluids, such as serum, urine and colostrum (Hanke et al, 2010;Link et al, 2010) have strengthened investigations into the use of miRNAs as non-invasive biomarkers of disease and a therapeutic response in a range of cancers including lung cancer, ovarian cancer, colorectal cancer, renal cancer, glioblastoma, prostate cancer and breast cancer (Cortez et al, 2012). In recent times, Lin et al (2014) characterized miRNAs expression profiles in cervical cancer of Uygur women to identify the biomarkers for early diagnosis.…”
Section: Micrornas As Potential Biomarkers For Cancer Diagnosis and Pmentioning
confidence: 99%
“…On the other hand, our data and others [25,27,28,[54][55][56][57][58][59][60][61][62][63][64][65][66] have shown that quantitative changes in the expression of few miRNA genes in stool or blood that are associated with colon cancer permit development of more sensitive and specific CRC molecular markers than those currently available on the market. In comparison to the commonly employed FOBT stool test, a noninvasive molecular and reliable test would particularly be more convenient as there would be no requirement for dietary restriction, or meticulous collection of samples, and thus a screening test would be acceptable to a broader segment of the population.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 54%
“…In comparison to the commonly employed FOBT stool test, a noninvasive molecular and reliable test would particularly be more convenient as there would be no requirement for dietary restriction, or meticulous collection of samples, and thus a screening test would be acceptable to a broader segment of the population. Using stable molecules such as miRNAs that are not easily degradable when extracted from stool or blood and manipulated thereafter, a miRNA -approach for colon cancer is thus preferable to a transcriptomic mRNA-, mutation DNA-, epigeneticor a proteomic-based test [25,27,[55][56][57][58][59][60][61][62][63][64][65][66][67][68], particularly that we and others have shown that these stable, nondegradable miRNA molecules can be easily extracted from stool or from circulation in vitro using commercially available kits. Advantages and disadvantages of the in vivo and in vitro tests are presented in table 1.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 99%